2020
DOI: 10.3389/fmicb.2020.02042
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Rhizosphere Bacteria, Fungi and Arbuscular Mycorrhizal Fungi Along an Elevational Gradient in a Temperate Montane Forest of China

Abstract: Elevational gradients strongly affect microbial biodiversity in bulk soil through altering plant and soil properties, but the effects on rhizosphere microbial patterns remain unclear, especially at large spatial scales. We therefore designed an elevational gradient experiment to examine rhizosphere microbial (bacteria, fungi and arbuscular mycorrhizal fungi) diversity and composition using Illumina sequencing of the 16S rRNA and ITS genes for comparison to plant and soil properties. Our results showed that bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
4
23
0
Order By: Relevance
“…Due to geographic separation, soil bacterial communities tend to display population stratification, such as elevational gradients, vertical depth, and horizontal distances. Among them, elevational gradients distinctively alter soils’ bacterial composition and diversity by affecting plant and soil properties compared with fine-scale spatial variations ( Guo et al, 2020 ). In the present study, the LDA results showed that the dominant bacterial indicators for rhizosphere were Variibacter , Rhodomicrobium , and Rhizobium from Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to geographic separation, soil bacterial communities tend to display population stratification, such as elevational gradients, vertical depth, and horizontal distances. Among them, elevational gradients distinctively alter soils’ bacterial composition and diversity by affecting plant and soil properties compared with fine-scale spatial variations ( Guo et al, 2020 ). In the present study, the LDA results showed that the dominant bacterial indicators for rhizosphere were Variibacter , Rhodomicrobium , and Rhizobium from Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…As a micro-environment of plant roots, the rhizosphere is an important site for soil-root-microorganism interaction ( Biddle et al, 2008 ; Bryant et al, 2008 ). Rhizosphere microorganisms are composed of many beneficial bacteria, playing profound roles in promoting plant growth and development ( Guo et al, 2020 ). Purposeful conservation of microbial communities is important for the survival and expansion of endangered plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of microbial diversity in mountain ecosystems reported different altitude-diversity patterns (Shen et al, 2013; Shen et al, 2014; Singh et al, 2014; Peay et al, 2017; Ren et al, 2018; Guo et al, 2020; Shen et al, 2020). Similar to the results of most studies based on high-throughput sequencing technology (Li et al, 2018; Shen et al, 2015; Shen et al, 2019), we found that soil bacterial diversity decreased with increasing altitude, however, the fungal diversity increased with altitude, which partially supported our first hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…However, only a few studies on the changes in fungal community composition along altitudinal gradients have been reported. Intriguingly, the altitudinal patterns of alpha diversity showed inconsistent or non-signi cant patterns [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 98%